Edukasi Pemasaran Melalui Marketplace pada Poklahsar Anggun di Desa Gondang Kecamatan Gangga Kabupaten Lombok Utara - Nasution, Ade Rezkika; Shelly Sylvia Agustina; Farah Ainun Jamil; Mutiara Mita Kasia; Eko Supriastuti (Universitas Mataram, 2025)
In North Lombok Regency, the Anggun Fish Farming Group (Poklahsar Anggun) is a fishery product processing and marketing group that produces locally sourced salted fish. Despite its sustainable production capabilities, its marketing activities are still limited to traditional markets. Several studies have shown that the use of social media and marketplaces not only serves as a promotional medium but also as a sales channel that can increase sales volume and marketing efficiency for small businesses. This community service activity focuses on expanding the target market through the use of social media and marketplaces as an adaptive and sustainable marketing strategy. The approach involves disseminating materials and direct practice. The implementation process is structured into three main stages: preparation, implementation, and evaluation. The use of Facebook Marketplace as the primary marketing medium has proven to be suitable for the group members' conditions and capabilities, particularly in addressing limited business capital. The implementation of an open order system is a relevant solution to minimize the risk of loss and reduce the need for initial capital for procuring raw fish. This strategy not only contributes to business sustainability but also opens up opportunities to expand market reach beyond traditional markets. The suggestion in this activity is for Poklahsar Anggun to manage its Facebook Marketplace account consistently and sustainably, then gradually expand the use of other digital marketing media such as WhatsApp Business and supporting social media.